The hunchback of Notre Dame II - Raymond, Bradley (Walt Disney Home Entertainment ; distributed by Viva Video, 2002)
Still the faithful protector of Notre Dame's beloved bells Quasimodo now rings them with the help of Esmeralda's and Phoebus' little boy, Zephyr, who is Quasi's best friend. Stopping with Zephyr at a travelling circus owned by the evil magician Sarousch, Quasi is captivated by Sarousch's lovely assistant, Madellaine. But greedy Sarousch is plotting to steal the Cathedral's most famous bell--with Madellaine's unwilling help. Surrounded by sorcery, betrayals and some laughably misguided advice from his gargoyle pals, Quasi listens to his own heart--and discovers that he, too, must look past appearances to find true love.